NETs Are Double-Edged Swords with the Potential to Aggravate or Resolve Periodontal Inflammation - Ljubomir Vitkov; Bernd Minnich; Jasmin Knopf; Christine Schauer; Matthias Hannig; Martin Herrmann (Cells, 2020)
Periodontitis is a general term for diseases characterised by inflammatory destruction of tooth-supporting tissues, gradual destruction of the marginal periodontal ligament and resorption of alveolar bone. Early-onset periodontitis is due to disturbed neutrophil extracellular trap (NET) formation and clearance. Indeed, mutations that inactivate the cysteine proteases cathepsin C result in the massive periodontal damage seen in patients with deficient NET formation. In contrast, exaggerated NET formation due to polymorphonuclear neutrophil (PMN) hyper-responsiveness drives the pathology of late-onset periodontitis by damaging and ulcerating the gingival epithelium and retarding epithelial healing. Despite the gingival regeneration, periodontitis progression ends with almost complete loss of the periodontal ligament and subsequent tooth loss. Thus, NETs help to maintain periodontal health, and their dysregulation, either insufficiency or surplus, causes heavy periodontal pathology and edentulism.